Different epistemic stances for different traumatic experiences: implications for mentalization - Ilaria Maria Antonietta Benzi; Nicola Carone; Laura Parolin; Gabriel Martin-Gagnon; Karin Ensink; Andrea Fontana (Research in Psychotherapy, 2023)
Traumatic experiences may impair reflective functioning (RF), making it difficult for individuals to understand their own and others' mental states. Epistemic trust (ET), which enables evaluating social information as reliable and relevant, may vary in association with RF. In this study, we explored the implications of different ET stances (i.e., trust, mistrust, and credulity) in the relation between different childhood traumatic experiences (i.e., emotional abuse, physical abuse, sexual abuse, emotional neglect, and physical neglect) and different types of RF impairments (uncertainty and certainty about mental states). A non-clinical community sample of 496 cisgender emerging adults (mage = 24.91, standard deviation = 2.66, 71.85% assigned female at birth, 63.63% heterosexual) reported on their childhood traumatic experiences, ET, and RF. We used structural equation models to examine direct and indirect associations. The results showed significant indirect effects between emotional abuse and uncertainty about mental states through credibility. We also observed significant indirect effects between emotional abuse and certainty about mental states through mistrust and credibility. The findings suggest that a lack of discrimination when evaluating knowledge from others (i.e., credulity) might promote increased uncertainty in RF when emerging adults have experienced emotional abuse in their childhood. Conversely, a tendency to view all information sources as unreliable or ill-intentioned (i.e., mistrust) may foster greater certainty in RF as a protective mechanism against an unreliable and potentially harmful world when combined with childhood emotional abuse. The implications for clinical practice and intervention are discussed.